2021
DOI: 10.1515/mlt-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of Puerto Rican university students displaced to South Florida after Hurricane Maria

Abstract: The purpose of this study is to document the experiences, services, and programs provided to displaced university students from Puerto Rico and to offer recommendations to educational and community agencies regarding effective integration after a natural disaster. Through in-depth semi-structured interviews, this qualitative phenomenology study consisted of collecting oral histories of six displaced university students from Puerto Rico who relocated to Southwest Florida after Hurricane Maria. The analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Meanwhile, following Hurricane Maria, Roque (2022) identified that participants experienced trauma and despair in the immediate months following the disaster. Furthermore, the participants in the study carried out by Szecsi et al (2023) specifically described the mental health toll of being displaced to the United States mainland, experiencing hardship due to resource mismanagement, and being treated as foreigners rather than Americans.…”
Section: Health and Wellbeing Impactsmentioning
confidence: 99%
“…Meanwhile, following Hurricane Maria, Roque (2022) identified that participants experienced trauma and despair in the immediate months following the disaster. Furthermore, the participants in the study carried out by Szecsi et al (2023) specifically described the mental health toll of being displaced to the United States mainland, experiencing hardship due to resource mismanagement, and being treated as foreigners rather than Americans.…”
Section: Health and Wellbeing Impactsmentioning
confidence: 99%